Environmental health risk assessment of dioxin in foods in Da Nang dioxin hot spot - Tran Thi Tuyet Hanh; Le Vu Anh; Nguyen Ngoc Bich; Hung Nguyen-Viet (2013)
Da Nang Airbase served as a bulk storage and supply facility for AO and other herbicides during the Operation Ranch Hand 1961-1971, and is currently one of the three most severe dioxin hot spots in Vietnam. This study applies the Australian Environmental Health Risk Assessment Framework aimed to assess the risk of dioxin exposure through foods for local residents living in An Khe, Hoa Khe, Chinh Gian and Thanh Khe Tay wards, surrounding a severe dioxin hot spot – the Da Nang Airbase. Various stakeholders were involved in the risk assessment process, and related publications on dioxin characteristics, its toxicity, and the levels in the local soil, mud, foods, milk, and blood samples were reviewed. A food frequency and knowledge - attitude – practice survey of 400 randomly selected local households from the four wards was conducted to provide data for exposure assessment. Results showed that local residents who have been consuming local cultivated high risk foods, especially freshwater fish, snails, crabs, free range chicken, duck, pumpkin, and lotus caught/raised/harvested inside or surrounding the Airbase would be at a very high risk. Their dioxin daily intake levels would exceed the recommended tolerable daily intake level recommended by WHO (1-4 pg/kg/day). Followed this risk assessment, a multi-approach risk reduction program was developed, implemented during 2010-2011 to reduce the risks of dioxin exposure for local residents.